2023
DOI: 10.1021/acsaenm.2c00174
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplastics Removal from Water using Metal–Organic Framework: Investigation of Adsorption Mechanisms, Kinetics, and Effective Environmental Parameters

Abstract: Nanoplastics are becoming a concern for the environment and are gaining significant attention due to their challenging removal process and ability to transport coexisting pollutants. Because of their mobility, small size (<1 μm), and accumulation tendency, nanoplastics are toxic for terrestrial and aquatic living organisms and humans, causing inflammation and oxidative stress. In this study, we investigated the removal of polystyrene nanoplastics (PSNPs) from water using a chromiumbased metal−organic framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…The results showed that the adsorption behavior best fitted the Freundlich adsorption model, which indicates the multilayer adsorption of MB onto the surface of the nanofiber and a heterogeneous surface of the nanofiber mats (adsorbent). 26 A kinetic study indicated that the adsorption mostly follows pseudo-1 st -order kinetics, which implies physisorption (electrostatic interaction) mechanism as discussed earlier. The kinetic study revealed the adsorption equilibrium of 5 h for the PVC pipe and PVC pool float fibers, 6 h for RG-PVC, 3% CaCO 3 -RG and 8% CaCO 3 -RG fibers, and 7 h for centrifuged PVC pipe fibers.…”
Section: Fiber Performance: Adsorption Model and Kineticsmentioning
confidence: 64%
See 2 more Smart Citations
“…The results showed that the adsorption behavior best fitted the Freundlich adsorption model, which indicates the multilayer adsorption of MB onto the surface of the nanofiber and a heterogeneous surface of the nanofiber mats (adsorbent). 26 A kinetic study indicated that the adsorption mostly follows pseudo-1 st -order kinetics, which implies physisorption (electrostatic interaction) mechanism as discussed earlier. The kinetic study revealed the adsorption equilibrium of 5 h for the PVC pipe and PVC pool float fibers, 6 h for RG-PVC, 3% CaCO 3 -RG and 8% CaCO 3 -RG fibers, and 7 h for centrifuged PVC pipe fibers.…”
Section: Fiber Performance: Adsorption Model and Kineticsmentioning
confidence: 64%
“…A minimum of three replicates of each solution were prepared and tested, and an average value was reported. The adsorption percentage was determined using eq % .25em normala normald normals normalo normalr normalp normalt normali normalo normaln = C normalo C normalf C normalo × 100 where C o is the initial concentration of MB in mg/L and C f is the final concentration of MB in mg/L.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Into another very recent study, published during the writing of this review, MIL-101(Cr) was studied as a potential adsorbent for the removal of PS NPs from MiliQ water [ 57 ] at different pH. The mean PS NPs particle size was 65 nm.…”
Section: Mofs As Mps/nps Adsorbentsmentioning
confidence: 99%
“… Entry MOF or MOF-based composite MPs/NPs Application Conditions Process efficiency Ref. 1 ZIF-67 PS (1–3 µm) Adsorbent 5 ppb of MPs in water at a 3–12 pH range, 288–308 K Up to 92.1% of removal at 298 K [ 56 ] 2 MIL-101(Cr) PS (65 nm) Adsorbent 5–100 ppm of NPs in MiliQ water at pH 5–10, 25°C Up to 96% of removal at 5 and 70 ppm, pH 5 [ 57 ] 3 UiO-66-X in a melamine porous foam, X = H, NH 2 , OH, Br and NO 2 PVDF 260–322 nm PMMA 325 nm PS 183 nm Adsorbent 0.5–2 ppm of MPs in water/ethanol (3:1) or simulated seawater environments PMMA, 88.2% PS 85.7% PVDF Up to 95.5% of removal [ 58 ] 4 ZIF-8 in a wood aerogel PVDF (60—110 nm) PS (90―140 nm) Adsorbent 0.5 ppm of MPs in water/ethanol (3:1) and seawater environments Up to 91.4% of removal [ 59 ] 5 PSF/MIL-100 (Fe) mixed matrix membrane PVC (134.6 µm) PE (42.5 µm) Adsorbent Different concentrations of MPs/Nps in water at different pHand in presence of MB Up to 99% of removal [ 60 ] 6 UiO-66(Zr) PET chips Catalytic degradation Solvent-free p...…”
Section: Introductionmentioning
confidence: 99%